أثر القيادة التحويلية على الالتزام التنظيمي للكوادر الصحية العاملة في مستشفى الأمير حمزة في الأردن - كناني، هبة عادل; الساعد، رشاد محمد (جامعة عمان العربية - عمادة البحث العلمي والدراسات العليا, 2020)
هدفت هذه الدراسة للتعرف إلى أثر القيادة التحويلية على الالتزام التنظيمي للكوادر الصحية العاملة في مستشفى الأمير حمزة في الأردن، واستخدم الباحثان المنهج الوصفي التحليلي للتعامل مع البيانات التي تصف المجتمع المبحوث والاستبانة في جمع البيانات المتعلقة بمتغيرات الدراسة وتحليلها بواسطة برنامج الحزم الإحصائية للعلوم الاجتماعية SPSS)) ووزعت الاستبانات على عينة عشوائية بسيطة تكونت من (310) موظفين (ذكورا وإناثا) بالمسميات التالية: (طبيب، وصيدلي، وممرض، وفني، وإداري)، وكان الصالح منها للتحليل (273) ويشكلون ما نسبته (88.1%) من عينة الدراسة. توصلت الدراسة إلى وجود أثر دال إحصائيا للقيادة التحويلية بأبعادها (التأثير المثالي، والاعتبار الفردي، والحافز الإلهامي، والاستثارة الفكرية) مجتمعة على الالتزام التنظيمي بأبعاده (الالتزام المستمر، والالتزام الأخلاقي، والالتزام العاطفي)، وكذلك أظهرت النتائج وجود أثر ذي دلالة إحصائية لكل بعد من الأبعاد (التأثير المثالي، والاعتبار الفردي، والحافز الإلهامي) منفردا على الالتزام التنظيمي، في حين أظهرت النتائج عدم وجود أثر ذي دلالة إحصائية لبعد الاستثارة الفكرية على الالتزام التنظيمي. وأوصت الدراسة بضرورة عقد ورشات العمل بهدف تعريف الكوادر الصحية برسالة المستشفى وأهدافها، وتحفيز الاستثارة الفكرية بتبني المستشفى سياسات يتبعها القادة تشجع على الناحية الإبداعية للكوادر الصحية العاملة في المستشفى.
The aim of this study is to examine the impact of transformational leadership on the organizational commitment of the health staff working in prince Hamza Hospital in Jordan. The researcher used the analytical descriptive approach to deal with the data describing the population and the questionnaire to collect the data on the variables of study which was analyzed by Statistical Package for Social Science software (SPSS). Questionnaires were distributed to a simple random sample consisting of (310) employees with the following positions: (doctor, pharmacist, nurse, technician and administrative) and (273) of which were valid for analysis and constituted (88.1%) of the study sample. The study showed a statistically significant impact of transformational leadership in its dimensions (idealized effect, individualized consideration and inspirational motivation and intellectual stimulation) on the organizational commitment in its dimensions(continuous commitment, moral commitment, emotional commitment), the results also showed a statistically significant impact for each dimension (idealized effect, individualized consideration, inspirational motivation) on the organizational commitment, while the results showed that there is no statistically significant impact of the dimension of intellectual stimulation on the organizational commitment. The study recommended the need to hold workshops in order to introduce health staff working to the mission of the hospital and its objectives and to motivate intellectual stimulation by adopting the hospital policies followed by the leaders encourage the creative aspect of the health staff working in the hospital.
Keywords: إدارة الموارد البشرية -- القيادة التحويلية -- الالتزام التنظيمي -- الكوادر الصحية